1996
DOI: 10.2307/1243775
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Elasticities in a Complete Food Demand System

Abstract: This study explores the linkage of the determinants of food choice with consumer nutrient availability by developing a procedure to measure changes in nutrient availability as the demand for food items change. It uses demand elasticities from traditional demand analysis to estimate elasticities of changes in the nutritional content of consumer diets. The procedure is applied to estimate nutrient elasticities for fifteen nutrients in response to changes in thirty-five food prices and per capita income. Copyrigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
76
1
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 10 publications
4
76
1
2
Order By: Relevance
“…In the latter, we show that all of the own-price elasticities are negative, except for alcohol for modest households, and almost all are significant and below one, except for red meat, fish, dried fruits, prepared meals, salt-fat products, and water. Furthermore, own-price elasticities for grain products, fruits, fruit juices, vegetables, and milk products are comparable to those reported by Huang (1996). We also found that modest households are significantly more sensitive than well-off households to own-price change for fish, dried fruits, milk products, cheese/butter/cream, oils, sugar-fat products, and mineral and spring waters but less sensitive for fresh vegetables and fruits and alcohol.…”
Section: Demand Elasticitiessupporting
confidence: 79%
See 2 more Smart Citations
“…In the latter, we show that all of the own-price elasticities are negative, except for alcohol for modest households, and almost all are significant and below one, except for red meat, fish, dried fruits, prepared meals, salt-fat products, and water. Furthermore, own-price elasticities for grain products, fruits, fruit juices, vegetables, and milk products are comparable to those reported by Huang (1996). We also found that modest households are significantly more sensitive than well-off households to own-price change for fish, dried fruits, milk products, cheese/butter/cream, oils, sugar-fat products, and mineral and spring waters but less sensitive for fresh vegetables and fruits and alcohol.…”
Section: Demand Elasticitiessupporting
confidence: 79%
“…The nutrient elasticities are calculated following the approach of Huang (1996) The crucial finding was that nutrient price elasticities are inelastic, as Huang and Lin (2000) and Beatty and LaFrance (2005) also found. Here, in table 5, to save space, we display only energy, saturated and polyunsaturated fat, sodium, calcium, beta-carotene, vitamin C, and magnesium elasticities for the 22 food categories across income class.…”
Section: Nutrient Elasticitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The second stage of the analysis is the use of a technique developed by Huang (1996) to explore the linkage of the demand model to nutrient availability. To do this, information about the nutrient values of each food consumed is needed.…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…This is referred to by Huang (1996) as the consumption technology of consumer behaviour. The values of a ki 's for non-foods will be assigned zero, thus the terms associated with non-foods will disappear.…”
Section: Methods Of Data Analysismentioning
confidence: 99%